PERKEMBANGAN HUKUM WARIS ADAT MINANGKABAU DALAM PEMBAGIAN WARISAN PADA MASYARAKAT MINANGKABAU DI ACEH (STUDI DI KECAMATAN TAPAKTUAN, ACEH SELATAN) - RIZKI MUTIA (PREMISE LAW JURNAL, 2016)
The Customary Inheritance Law in Indonesia is highly influenced by the kinship system relevant to the related community. To Minangkabau people who have settled permanently in other regions (perantauan) like Tapaktuan Subdistrict, can have different views on the implementation of their customary law, particularly in inheritance system. The research used a judicial empirical and descriptive analytic method. 86.6% of the Minangkabau community that settles in Tapaktuan Subdistrict nowadays implements Acehnese customary law in distributing inheritance. The procedures are as follows: a)excluding the rights related to the inheritance, (b)involving Religious Leader to carry out the distribution of inheritance (some of them in with the family relationship), (c) deciding who the heirs are, (d)determining the share of each heir, (e)performing the inheritance distribution. The obstacles that discourage the implementation of Minangkabau Customary Inheritance Law in Tapaktuan Sub-district are: a)the influence of the religious belief, b)marriage, c)the absence of witness from Minangkabau community Keywords: Inheritance Law, Minangkabau Customary Inheritance, Acehnese Customary Inheritance